Chrysin isolated from Pyrus pashia fruit ameliorates convulsions in experimental animals - Sharma P.; Kumari A.; Gulati A.; Krishnamurthy S.; Hemalatha S. (My University, 2025)
Objective: The traditional use of the ethanolic extract of the fruit of Pyrus pashia (EPP) as a potential anticonvulsant was validated using experimental animal models. Furthermore, the anticonvulsant activity of isolated chrysin was investigated against experimental animal models to draw a possible therapeutic mechanism of EPP. Additionally, the safety profile of chrysin was evaluated to explore the possible therapeutic alternative in the management of epilepsy. Method: The anticonvulsant activity in terms of duration of onset of hind limb tonic extension and convulsion of standardized EPP was evaluated against maximal electroshock (MES) and pentylenetetrazole (PTZ) model of experimental epilepsy respectively. Furthermore, the anticonvulsant activity and electrophysiological properties of chrysin was investigated in addition to antioxidant activity against PTZ-induced convulsion in experimental animals. Moreover, the neurotoxic profile of the chrysin was assessed in terms of duration of movement and running in photoactometer and rotarod apparatus, respectively. Results: EPP (100, 200, and 400 mg/kg) exhibited significant anticonvulsant activity against an acute model of MES and PTZ-induced convulsions in experimental animals. Furthermore, chrysin (2.5, 5, and 10 mg/kg) also exhibited significant anticonvulsant activity against PTZ-induced convulsions in rats. In addition, chrysin did not exhibit sedative-like behavior in experimental rodents. Discussion: EPP could be considered as a potential and alternative therapeutic option in the management of epilepsy. © 2017, © 2017 Informa UK Limited, trading as Taylor & Francis Group.